2016
DOI: 10.3168/jds.2016-10910
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Effect of oregano and caraway essential oils on the production and flavor of cow milk

Abstract: Many essential oils and their terpene constituents display antimicrobial properties, which may affect rumen metabolism and influence milk production parameters. Many of these compounds also have distinct flavors and aromas that may make their way into the milk, altering its sensory properties. Essential oils from caraway (Carum carvi) seeds and oregano (Origanum vulgare) plants were included in dairy cow diets to study the effects on terpene composition and sensory properties of the produced milk, as well as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 19 publications
3
28
1
1
Order By: Relevance
“…Dry matter intake was not affected by feeding low or high EO oregano, indicating that the doses of oregano fed to cows did not affect diet palatability. In agreement, DMI was not affected when feeding oregano material (Tekippe et al, 2011) or oregano EO (Wang et al, 2009;Lejonklev et al, 2016). In contrast, Hristov et al (2013) observed a linear decrease in DMI with increasing oregano doses.…”
Section: Dmi and Milk-related Variablessupporting
confidence: 55%
See 1 more Smart Citation
“…Dry matter intake was not affected by feeding low or high EO oregano, indicating that the doses of oregano fed to cows did not affect diet palatability. In agreement, DMI was not affected when feeding oregano material (Tekippe et al, 2011) or oregano EO (Wang et al, 2009;Lejonklev et al, 2016). In contrast, Hristov et al (2013) observed a linear decrease in DMI with increasing oregano doses.…”
Section: Dmi and Milk-related Variablessupporting
confidence: 55%
“…In vivo evidence on the effectiveness of oregano EO, as such, is not consistent (Wang et al, 2009;Hristov et al, 2013;Lejonklev et al, 2016;Kolling et al, 2018). The effectiveness might depend on the dosage and mode of inclusion (plant material or EO).…”
mentioning
confidence: 99%
“…A concern about the use of aromatic plants and EOs as food additive in milk‐producing farm animals is that their flavors and aromas may make their way into the milk, altering its sensory properties. Two levels of essential oils of caraway and oregano (0.2 and 1.0 g of oil/kg of dry matter) were added to the feed of lactating cows for 24 d in a study of 2016 . With this treatment, the amount and composition of volatile terpenes were altered in the produced milk, and the sensory properties of the produced milk were altered as well, and milk samples from animals receiving essential oil treatment were perceived as having a fresher aroma and lower stored aroma and flavor.…”
Section: Essential Oils: Very Old ‘Guys’ With Great Prospectsmentioning
confidence: 99%
“…Two levels of essential oils of caraway and oregano (0.2 and 1.0 g of oil/kg of dry matter) were added to the feed of lactating cows for 24 d in a study of 2016. [250] With this treatment, the amount and composition of volatile terpenes were altered in the produced milk, and the sensory properties of the produced milk were altered as well, and milk samples from animals receiving essential oil treatment were perceived as having a fresher aroma and lower stored aroma and flavor. Interesting are the studies on the effects of EOs dietary supplementation on animals under stress conditions.…”
Section: Diet Supplement For Animal Feeding and Application For Animamentioning
confidence: 99%
“…Milk samples were easily distinguishable by their volatile profile based on feeding system, storage time, and pasteurization.Molecules 2020, 25, 26 2 of 28 of forage type on milk fat and composition, and highlighted the need to evaluate the impact of feeding systems on other aspects of milk fat quality, such as flavor and oxidative stability. Milk produced from many supplemented and altered diets have been investigated, including supplementation with flaxseed [8], lipid complex [9], crude protein [10], iodine [11] marine algae [12], oregano and caraway essential oils [13], hull-less barley [14] and sunflower/fish oil [15]. These studies focused mainly on animal production performance, milk composition, milk yield, milk fatty acid composition, and to a lesser extent on the flavor and sensory characteristics of milk.…”
mentioning
confidence: 99%